GLOBAL ISSUES (POVERTY POLLUTION EQUALITY) (Ustozlar uchun, 2025)
This thesis examines the interconnected global issues of poverty, pollution, and inequality, arguing that they form a mutually reinforcing cycle. Poverty often forces communities to rely on environmentally harmful practices, which increases pollution levels. In turn, pollution disproportionately affects low-income populations, creating health problems, economic barriers, and reduced social mobility. Structural inequality—particularly unequal access to resources, political power, and environmental protection—deepens this cycle and makes it difficult for marginalized groups to improve their living conditions. The study concludes that addressing these global challenges requires integrated solutions that combine environmental justice, sustainable development, and fair economic policies.